2014
DOI: 10.1098/rspb.2014.0696
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical limits to maximum weapon size in a giant rhinoceros beetle

Abstract: The horns of giant rhinoceros beetles are a classic example of the elaborate morphologies that can result from sexual selection. Theory predicts that sexual traits will evolve to be increasingly exaggerated until survival costs balance the reproductive benefits of further trait elaboration. In Trypoxylus dichotomus, long horns confer a competitive advantage to males, yet previous studies have found that they do not incur survival costs. It is therefore unlikely that horn size is limited by the theoretical cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…Results from the finite element models indicate that the highest stresses generated in a horn during fights occur in the middle of the shaft, which matches the actual location of horn fractures for beetles in the field (39). Our finite element models therefore accurately predict the responses of horns to the forces incurred during fights.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…Results from the finite element models indicate that the highest stresses generated in a horn during fights occur in the middle of the shaft, which matches the actual location of horn fractures for beetles in the field (39). Our finite element models therefore accurately predict the responses of horns to the forces incurred during fights.…”
Section: Methodssupporting
confidence: 57%
“…Specifically, to compare performance in terms of model stress (σ = F=A, where F is force and A is cross-sectional surface area) in the vertical and lateral bending models, we maintained the same force-to-surface area ratios (36). The three models were therefore scaled to the same surface area (723 mm 2 , or the surface area of the Trypoxylus model), and the same total force (4 N) was applied to the horn tip, based on field estimates of the forces exerted by Trypoxylus males during fights (39). Similarly, to compare stress in our twisting models, we maintained the same torque-tovolume ratios.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, males manage to retain their safety factor at approximately the same level as that of female jaws, despite their strongly increased bite muscle force. The safety factors that we measured (5.2-7.2) are comparable to other measurements of male C. metallifer stag beetle jaws (2.05-12.7) and to those of rhinoceros beetle horns (6.5) [17,18].…”
Section: Intersexual Differencessupporting
confidence: 87%
“…An important possible trade off between reproductive benefits and survival costs is the mechanical or structural strength of the weapon. Studies on the structural strength of horns on the rhinoceros beetle, Trypoxylus dichotomus , suggested that as the horn length increased, so did the force that was required to break the horn, indicating that longer horns can withstand higher forces and that there is increased material reinforcement in longer horns (McCullough, ). Our findings show that the force required to break a mandible did not increase with mandible length, but rather stayed relatively constant across mandible lengths.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there are mechanical limits to the size of the horn in rhinoceros beetles, resulting in decreased safety factors as the horn length increases (McCullough, ). This same trend was found in our data.…”
Section: Discussionmentioning
confidence: 99%